Microemulsion-based peanut oil extraction using surfactant solution - Nur Syafiqah Amira, Binti Mohd Zulkefli (Universiti Malaysia Sarawak, UNIMAS, 2012)
Nowadays, vegetable oil is an alternative for the substitution of biodiesel. Vegetable oil extraction is more favourable by using surfactant compared to hexane which is hazardous to human. In this study, extraction efficiency and physical appearance of oil extracted by Brij-30, GE-460 and their mixture were evaluated at optimum conditions. Microemulsionbased extraction was conducted by mixing these surfactants with ground peanut samples (0.2-0.5mm) and agitated at 150 rpm. This enables the oil to be collected because it’s liberated from the samples as a separate phase from the aqueous phase. Contact time, concentration of surfactant, weight of samples and types of surfactant on oil yield were tested to identify optimum extraction conditions. After optimum conditions were achieved, solvent based extraction using hexane was done by soxhlet method for comparison. The oil collected from both extractions was compared based on their extraction efficiencies, physical appearance of oil and Fourier Transform Infrared Spectroscopy (FTIR) characterization. The appearance of oil extracted using surfactant showed lighter yellow colour and did not produced any odour compared to hexane extraction. Optimum extraction of 87.15% was achieved at weight of sample of 1g, 30 minutes extraction at 150 shakes/min, and 0.015M surfactant concentration while the extraction efficiency for mixed surfactant of GE-60 and Brij-30 was 92.93% in the ratio of Brij-30 to GE-460 of 3:1. Percentage of extraction using solvent is 91.37% which is higher compared to microemulsion-based extraction. The FTIR characterization on both methods shows not much difference due to the same source of origin. The formation of oil was proven by ester formation that was detected at 1743cm-1.